Explaining informal payments in the Romanian public health care system - Răzvan-Ionuț Drugă (CES Working Papers, 2022)
Informal payments in the public health care system represent one of the most sensitive topics in the medical world. It is also a subject of interest for many researchers. As evidenced by reports from various European institutions, a catalyst for their use was the COVID-19 pandemic. Among all the countries of the European Union, Romania was reported with the highest rate of use of these payments. With the support of parallel marketing research, carried out both among patients in Romania and among medical staff, it is demonstrated that they do not consider such practices natural. However, following the conclusions, in order to stop this trend, it is recommended, among other things, to reduce the institutional asymmetry, to tighten the penalties for the medical staff who accept such payments or to stimulate the medical staff, by increasing their salaries.
Keywords: 330; informal payments; COVID-19; patients; public health care system; institutional asymmetry